2010
DOI: 10.1007/s11999-009-1182-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Joint Hypermobility Syndrome in a Military Population: Impact of Gender and Race

Abstract: Background Joint hypermobility syndrome is defined by abnormal laxity in multiple joints in association with symptomatic joint pain. Previous studies in small populations suggest a predominance of female gender and nonwhite race among those diagnosed with hypermobility syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
(61 reference statements)
2
12
0
1
Order By: Relevance
“…11 While not part of this review, several studies indicate that females also have increased generalized laxity throughout all joints in the body compared with males, [62][63][64][65] which may be related to hormonal status. 66 Hypermobility has been associated with OA [67][68][69] and females have higher rates of hypermobility 70 and knee OA. 71 Increased joint laxity may be an unmodifiable risk factor for women but more research is needed to rule out other sex differences as the cause of increased OA prevalence in females.…”
Section: Discussionmentioning
confidence: 99%
“…11 While not part of this review, several studies indicate that females also have increased generalized laxity throughout all joints in the body compared with males, [62][63][64][65] which may be related to hormonal status. 66 Hypermobility has been associated with OA [67][68][69] and females have higher rates of hypermobility 70 and knee OA. 71 Increased joint laxity may be an unmodifiable risk factor for women but more research is needed to rule out other sex differences as the cause of increased OA prevalence in females.…”
Section: Discussionmentioning
confidence: 99%
“…As the diagnoses of lumbar radiculopathy in this investigation were made entirely by practitioners not involved in this study, we were also reliant on the clinical and diagnostic acumen of others to a substantial degree. However, prior studies have found that diagnostic coding error is low in database reporting, 20,22 and the DMED contains provisions which attempt to ensure accurate data acquisition and validation. 23 Other limitations to this study include the fact that potentially important prognostic factors for lumbar radiculopathy, such as body mass index and smoking status, were not available in this system.…”
Section: Discussionmentioning
confidence: 99%
“…The DMED prospectively captures medical and demographic data for all individuals serving in the United States Armed Forces and has been successfully used in estimating the epidemiology of orthopedic conditions in the past. [15][16][17][18][19][20] The DMED records all medical diagnoses given to servicemembers during their time in the military by International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code. The DMED gathers data from the Department of Defense Ambulatory Data System and the Composite Health Care System so that all medical diagnoses rendered to an individual in any healthcare setting are captured in the database.…”
mentioning
confidence: 99%
“…In contrast, Al-Rawi et al performing their study among 1774 students aged 20-24 years using the Beighton score found that the incidence rate of joint hypermobility was higher in women (38.5%) than in men (25.4%) [6]. Similar results were reported by Scher et al (the incidence rate quotient for women -0.15 whereas for men -0.04) [7]. of individuals (335/750) and was more common in girls (58.9%, 238/404) than in women (36.5%, 97/266).…”
Section: Resultsmentioning
confidence: 49%
“…Our divergent findings can suggest that age differences in the study population were too small and resulted in the higher mean age of students with severe joint hypermobility syndrome compared to the mean age of those without the syndrome. that the incidence rate quotient amongst Caucasian members of the Defense Medical Database was 1.44 compared to 1.34 amongst the remaining members and was higher (p=0.0006) than that in Black members of the above Database [7]. Moreover, according to Klemp et al, the incidences of joint hypermobility syndrome were 6.2 for the Maoris (9.0 for women, 2.2 for men) and 4.0 for the Europeans living in New Zealand (5.6 and 1.9) [11].…”
Section: Resultsmentioning
confidence: 76%